Kekerasan Verbal Terhadap Istri Di Dalam Rumah Tangga - Juwita Mutiara Sintha; Yuarini Wahyu Pertiwi (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2025)
The issue of verbal violence in households is a form of violence that frequently occurs but is unfortunately less recognized by society. This form of violence involves the use of words and language that demean, insult, or threaten by one or both parties in a husband-wife relationship or within the family environment, causing psychological impacts on the victims. The purpose of this research is to provide information so that society becomes aware and can implement preventive measures. This research uses a literature study method by reviewing various sources, such as scientific journals and research reports, to provide an overview of verbal violence in households, including its causes, impacts, and preventive efforts. The research results show that verbal violence affects the mental health of victims, including decreased self-esteem, anxiety, and prolonged depression. Economic factors, patriarchal culture, and the lack of healthy communication in families are the main triggers. With better understanding of verbal violence in households, it is hoped to provide knowledge to reduce the occurrence of verbal violence in households, thus creating a safe and comfortable family environment.